DESIGN DRY CABINET MENGGUNAKAN MICROCONTROLLER ESP 32 - Al Faruqi, Ismail; Kusmantor, Adhi (Universitas Semarang, 2024)
Dry Cabinet is a highly useful tool, looking at the highly advanced era and tools that require special conditions are very unfortunate if damage occurs. The optimal relative humidity used for camera lens storage ranges from 35% - 60%. Another example for items that require a certain humidity is medicines. Optimalization humidity for storing medicines is under 60%. This Dry cabinet design uses an ESP32 micro controller, there are supporting components for the HTU 21 D temperature sensor, LCD, relay, LED, 3 volts AMS Stepdown, and Push button. The purpose of this research is to make it easier for humans to store goods that require special monitoring of humidity. With HTU21D temperature and humidity meters, the temperature and humidity in the Dry Cabinet Room can be measured. The method in this study uses 3 stages of initiation of temperature recognition by the HTU21D sensor, then setting the desired set point, and has an output in main-taining the desired humidity. The results in this study, based on temperature and humidity testing, humidity can reach the optimal set point at 35% - 40% humidity, and takes 2 hours. When the heatsink is on the humidity will decrease and when the heatsink is off the humidity will increase. Range for the temperature in the dry cabinet room is 30 to 33 degrees Celsi-us. Keywords: Dry Cabinet, ESP 32, HTU21D, Humidity, Temperature ABSTRAK Dry Cabinet merupakan alat yang berdaya guna tinggi, dengan melihat pada zaman yang sangat maju dan alat – alat yang membutuhkan kondisi khusus amat di sayang jika terjadi kerusakan. Kelembaban relatif yang optimal digunakan untuk penyimpanan lensa kamera berkisar antara 35% - 60%. Contoh lain untuk barang yang membutuhkan kondisi kelembaban tertentu ialah obat – obat tan, kelembaban yang optimal untuk menyimpan obat – Obata tan berkisar dibawah 60%. Rancangan Dry cabinet ini menggunakan micro controller ESP32, terdapat komponen pendukung sensor suhu HTU 21 D, lcd, relay, LED, Stepdown AMS 3 volts, dan Push button. Tujuan dari penelitian tersebut agar mempermu-dah manusia dalam menyimpan barang – barang yang membutuhkan pemantauan khusus terhadap kelembaban Dengan pengukur suhu dan kelembaban HTU 21 D, suhu dan kelembaban pada Ruang Dry Cabinet dapat terukur. Metode dalam penelitian ini menggunakan 3 tahapan inisiasi pengenalan suhu oleh sensor HTU21D, kemudian pengaturan set point yang di inginkan, dan memiliki output dalam mempertahankan kelembaban yang diinginkan. Hasil dalam penelitian ini, berdasarkan pengujian suhu dan kelembaban yang dapat di pertahankan pada kelembaban 35% - 40% membutuhkan waktu selama 2 jam. Saat heatsink hidup kelembaban akan menurun dan saat heatsink mati kelembaban akan naik. untuk suhu pada ruang dry cabinet tersebut berkisar 30 hingga 33 derajat celsius.